Comparative study of shortening and cutting strategies of single-walled and multi-walled carbon nanotubes assessed by scanning electron microscopy. (November 2018) - Kierkowicz, Magdalena; Pach, Elzbieta; Santidrián, Ana; Sandoval, Stefania; Gonçalves, Gil; Tobías-Rossell, Ester; Kalbáč, Martin; Ballesteros, Belén; Tobias, Gerard
Abstract: Short carbon nanotubes (CNTs) are desired for a variety of applications. As a consequence, several strategies have been reported to cut and shorten the length of as-produced CNTs via chemical and physical routes. The efficiency of a given strategy largely depends on the physico-chemical characteristics of the CNTs employed. In order to be able to directly compare the advantages and disadvantages of commonly used protocols, a single batch of chemical vapor deposition single-walled CNTs (SWCNTs) and a batch of multi-walled CNTs (MWCNTs) were subjected to four cutting/shortening strategies, namely acid cutting, piranha treatment, steam shortening and ball milling. The length distribution was assessed by means of scanning electron microscopy. Sample purity and CNT wall structure were determined by Raman spectroscopy, thermogravimetric analysis and magnetic measurements. Within the employed experimental conditions, piranha treatment turned out to be the most efficient to achieve short SWCNTs with a narrow length distribution in a good yield, whereas a mixture of sulfuric/nitric acid was preferred in the case of MWCNTs. A subsequent short steam treatment allowed to remove functional groups present in the samples, leading to median length distributions of 266 nm and 225 nm for SWCNTs and MWCNTs respectively after the combined protocols. Graphical abstract: Image 1